2016
DOI: 10.1021/acs.molpharmaceut.6b00280
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Characterization of a Pro-Antibody–Drug Conjugate by LC–MS

Abstract: Pro-antibody-drug conjugate (PDC) is a hybrid structural format of immunoconjugate, where the structural complexity of pro-antibody and intrinsic heterogeneity of ADCs impose a prominent analytical challenge to the in-depth characterization of PDCs. In the present study, we successfully prepared and characterized PanP-DM1 as a model of PDCs, which is an anti-EGFR pro-antibody following conjugation with DM1 at lysine residues. The drug-to-antibody ratio (DAR) of PanP-DM1 was determined by LC-MS after deglycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…23,46 Characterization of IAB by SEC-UPLC, LC-MS, and competitive ELISA The homogeneity of IAB were verified by size-exclusion chromatography-ultra performance liquid chromatography (SEC-UPLC) and molecular weight was accurately measured by LC-MS, as previously described. 47,48 The CD47/PD-L1 binding activity of IAB was evaluated by competitive ELISA. Briefly, ELISA plates (Costar) were coated overnight at 4 Cwith hPD-L1 Fc (Shanghai Sinomab Biotech Co., ZJ-01-041) or hCD47 Fc (Shanghai Sinomab Biotech Co., ZJ-01-053) in phosphate-buffered saline (PBS) buffer.…”
Section: Bispecific Fusion Protein Expression and Purificationmentioning
confidence: 99%
“…23,46 Characterization of IAB by SEC-UPLC, LC-MS, and competitive ELISA The homogeneity of IAB were verified by size-exclusion chromatography-ultra performance liquid chromatography (SEC-UPLC) and molecular weight was accurately measured by LC-MS, as previously described. 47,48 The CD47/PD-L1 binding activity of IAB was evaluated by competitive ELISA. Briefly, ELISA plates (Costar) were coated overnight at 4 Cwith hPD-L1 Fc (Shanghai Sinomab Biotech Co., ZJ-01-041) or hCD47 Fc (Shanghai Sinomab Biotech Co., ZJ-01-053) in phosphate-buffered saline (PBS) buffer.…”
Section: Bispecific Fusion Protein Expression and Purificationmentioning
confidence: 99%
“…• Cetuximab [35] • anti-VCAM-1 Ab [43] • Panitumumab (anti-EGFR mAb) [193] • Panitumumab-DM1 [93,192] • anti-HIV p17 Ab [70] of immunogenicity of anti-Hinge Ab from the host; (3) Ab lock can significantly inhibit the binding and neutralizing ability of anti-idiotypic Ab to original Ab drugs, at least in the case of Infliximab; (4) The changeable design of protease substrate between Ab lock and Infliximab can be applied to any alternative Ab drugs that are used for RA or even other disease treatments. It is expected that a protease cleavable and efficient Ab lock can significantly increase the selective activation of Ab drugs at the disease site and reduce the on-target toxicities of Ab drugs during systemic circulation, thus potentially improving the clinical benefit and quality of life of patients.…”
Section: Different Masking Strategies For Pro-antibody Drug Developmentmentioning
confidence: 99%
“…Similar strategies were also applied to other Abs such as anti-vascular cell adhesion molecule 1 (VCAM-1) mAb [43] and anti-EGFR mAb (Panitumumab, Vectibix®) [193]. Furthermore, Liu et al [93] and Yang et al [192] applied the Probody approach to the maytansine (DM1)conjugated anti-EGFR mAb (Panitumumab) and generated a pro-antibody-drug conjugate (PDC) named PanP-DM1. Regardless of DM1 conjugation, the PanP-DM1 still displayed 12-fold weaker binding ability to immobilized EGFR antigen than parental Panitumumab and significantly improved the cancer-selective activity, therapeutic and safety index over traditional ADC.…”
Section: Affinity-peptide Based Ab Lock Affinity Peptidementioning
confidence: 99%
“…Average DAR of ADCs pool containing different drug load can be determined using UV-Vis spectroscopy. Average DAR for ADCs with drugs like vinca alkaloid 4-desacetylvinblastine-3-carbohydrazide (DAVLB), 13 methotrexate, 14 adriamycin, 15 and monomethyl auristatine E (MMAE), 16 maytansinoid, 17 emtansine 18 have been successfully determined. Hamblett et al have demonstrated the validity of DAR determined by UV-Vis method using hydrophobic chromatography.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%